The impact of routines on emotional and behavioural difficulties in children and on parental anxiety during COVID-19 - Lees, Vera; Hay, Rosie; Bould, Helen; Kwong, Alex S. F.; Major-Smith, Daniel; Kounali, Daphne; Pearson, Rebecca M. (Frontiers in Child and Adolescent Psychiatry, 2023)
Background. The Covid-19 pandemic and related public health measures, including lockdowns and school closures, have impacted on mental health of children. We hypothesised that there would be an association between maintaining a routine during lockdown and both lower emotional and behavioural difficulties in children and lower parental anxiety. We also hypothesised that children of 'keyworker' parents would have fewer emotional and behavioural symptoms due to having maintained more normal routines. Keyworker status was defined as those whose work was essential to Covid-19 response We used data from ALSPAC to explore associations between maintaining a routine, and emotional and behavioural difficulties in children, using linear regression models. We included measures of parental anxiety. We separately explored associations with having a keyworker parent. We used the Carey Infant Temperament Questionnaire and the Revised Rutter Parent Scale for Preschool Children to establish levels of emotional and behavioural difficulties. The measures were chosen to match previous waves in multi-generations in ALSPAC where they had been shown to be predictive of later mental health in children. The scales measure emotional and behavioural problems. Results. 289 parents completed questionnaires about their 411 children. Keeping a routine was associated with emotional and behavioural difficulty scores 5.0 points lower (95% CI -10.0 to -0.1), p=0.045 than not keeping a routine. Parents who reported keeping a routine had anxiety scores 4.3 points lower (95% CI -7.5 to -1.1), p=0.009 than those who did not. Children of keyworkers tended to have lower emotional and behavioural difficulty scores (-3.1 (95%CI -6.26 to 0.08), p=0.056) than children of non-keyworkers. All models were adjusted for relevant potential confounders. The magnitude of change in anxiety scores is considered clinically meaningful, with such changes in symptoms of similar magnitude being associated with improvement following clinical interventions like Cognitive Behavioural Therapy (CBT) and perceived feelings of feeling better. 1 Conclusion. Maintaining a routine may be beneficial for both child emotional wellbeing and parental anxiety, although it is also possible that lower parental anxiety levels made maintaining a routine easier. Being the child of a keyworker parent during lockdown may have been protective for child emotional wellbeing.